The behavioral and neural basis of empathic blame - Indrajeet Patil (Nature Portfolio, 2017)
Abstract Mature moral judgments rely both on a perpetrator’s intent to cause harm, and also on the actual harm caused–even when unintended. Much prior research asks how intent information is represented neurally, but little asks how even unintended harms influence judgment. We interrogate the psychological and neural basis of this process, focusing especially on the role of empathy for the victim of a harmful act. Using fMRI, we found that the ‘empathy for pain’ network was involved in encoding harmful outcomes and integrating harmfulness information for different types of moral judgments, and individual differences in the extent to which this network was active during encoding and integration of harmfulness information determined severity of moral judgments. Additionally, activity in the network was down-regulated for acceptability, but not blame, judgments for accidental harm condition, suggesting that these two types of moral evaluations are neurobiologically dissociable. These results support a model of “empathic blame”, whereby the perceived suffering of a victim colors moral judgment of an accidental harmdoer.